Studi Kualitatif Dinamika Perilaku Mencari Bantuan pada Mantan Pecandu Narkoba Multi Zat - Bianca Alia Sudewaji; Lifina Dewi Pohan (Humanitas (Jurnal Psikologi), 2022)
The number of drug users in Indonesia increased during the COVID-19 pandemic. Meanwhile, people seeking rehabilitation for quitting drugs are also growing these past two years according to Badan Narkotika Nasional (BNN) report in 2020 and 2021. Help-seeking behavior is important for individuals with physical and mental health disorders to get treatment. Research shows that help-seeking behavior on the problem of substance abuse has many barriers and driving factors. The study aims to look at the dynamics of help-seeking behavior in former multi-substance drug addicts who have managed to quit completely since 2013. The research is single case study, focusing on the participant's experience of realizing the addiction problem and seeking treatment. Data obtained through interview via google meet. The participant is male 48 years old former addict to various drugs since 1997, quit entirely in 2013, undergo therapeutic community selected by purposive sampling. The researcher also collecting data from expert in the last rehabilitation facility for triangulation. Thematic analysis results are the participant’s background and drug use, treatment history, help-seeking behavior, and problem resolution. The participant achieved full recovery due to adequate social support from family and rehabilitation facility, firmly committed to change, and avoiding negative environment.